Pan-immune-inflammation value and its association with all-cause and cause-specific mortality in the general population: a nationwide cohort study - Ye Zhang; Yong Yue; Yong Yue; Zhengyu Sun; Pengcheng Li; Xiaoyi Wang; Gang Cheng; Hailin Huang; Zongping Li (Frontiers in Endocrinology)
IntroductionThe Pan-Immune-Inflammation Value (PIV) is a novel biomarker derived from counts of neutrophils, platelets, monocytes, and lymphocytes, providing a comprehensive measure of systemic immune and inflammatory status. While it has shown prognostic value in specific disease settings, its association with mortality in the general population remains unclear. This study aims to evaluate the predictive value of PIV for all-cause and cause-specific mortality, including cardiovascular, cancer, and diabetes-related deaths, within a general adult population.MethodsData were obtained from the NHANES cohort, with 48,662 participants aged 20 and older. Participants were followed for an average of 117.44 months, with PIV quartiles calculated at baseline. Cox proportional hazard models were used to assess mortality risk across PIV quartiles, while restricted cubic spline models examined nonlinear dose-response relationships. Subgroup and sensitivity analyses further explored the robustness of PIV’s associations.ResultsHigher PIV levels were significantly associated with increased risks of all-cause, cardiovascular, cancer, and diabetes mortality. Nonlinear relationships were observed between PIV and all-cause, cardiovascular, and cancer mortality, with a risk threshold at PIV values above 254.07. Subgroup analyses supported these findings, and sensitivity analyses confirmed the consistency of PIV’s prognostic value.ConclusionElevated PIV serves as an independent risk factor for multiple mortality outcomes in the general population. This study underscores the potential of PIV as a predictive biomarker for mortality risk, with implications for its use in clinical and epidemiological settings. Further studies are needed to confirm PIV’s clinical utility across diverse populations and conditions.